PENENTUAN JUMLAH BAKTERI, KADAR PROTEIN DAN SIFAT ORGANOLEPTIK DAGING AYAM BROILER (Gallus domesticus) SETELAH DIRENDAM DALAM LARUTAN LIDAH BUAYA (Aloe vera) - Imro'atu Warda; Susie Amilah (FMIPA : Universitas PGRI Adi Buana, 2016)
The solvents of aloe (Aloe vera) are known to be used as an antibacterial. This study aims to prove the antibacterial activity in broiler chicken meat (Gallus domesticus), the variables were observed in this studythe number of bacteria, protein content and organoleptic properties of broiler meat soaked in a solvents ofaloe vera. Aloe vera is obtained from MIPA laboratory of blender, then dissolved in aquadest. This study wasconducted using a completely randomized experimental design consisting of 5 concentration of aloe vera (0,25, 30, 35, 40 g / 100ml) with 4 replications. The results showed that the concentration of aloe significanteffect (P<0.05) against the number of bacteria on broiler chicken meat. However, no significant effect (P>0.05) on protein content and organoleptic properties. Results of this study indicate that aloe vera solventsconcentration of 25 g / 100 ml can be used to preserve meat broiler without altering the protein contentand organoleptic properties. Keywords: broiler chicken meat, Aloe vera, bacteria, proteins, organoleptic